2015
DOI: 10.1007/s40261-015-0312-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food on the Pharmacokinetics of Piperaquine and Dihydroartemisinin

Abstract: Although food was found to significantly impact on the pharmacokinetics of piperaquine and dihydroartemisinin, given the low fat content of standard meals within endemic regions and the anorexic effects of malaria infection, these results are unlikely to impact on the clinical utility of these drugs. However, co-administration of food with these anti-malarials by populations consuming a typical Western diet should be avoided to reduce the risk of toxic side effects. It is therefore a general recommendation tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The PPQ PK properties are in good agreement with other studies in healthy volunteers administered the drug alone [33][34][35][36] or coadministered with DHA. 37,38 Similar to other studies, multiple peaks were observed in the PPQ concentration-time profiles of 82% (18 of 22) of participants.…”
Section: Discussionsupporting
confidence: 88%
“…The PPQ PK properties are in good agreement with other studies in healthy volunteers administered the drug alone [33][34][35][36] or coadministered with DHA. 37,38 Similar to other studies, multiple peaks were observed in the PPQ concentration-time profiles of 82% (18 of 22) of participants.…”
Section: Discussionsupporting
confidence: 88%
“…The oral clearance and apparent oral volume of distribution of PQ have been found to be lower in patients than in healthy subjects (29). PQ exposure was increased (ϳ3-fold) when administered with a high-fat/high-calorie meal (30). In addition, a shorter half-life (14 days) of PQ was found in children, and children had a CL/F (1.8 liters/h/kg) more rapid than that in adults (31), which probably reflects higher rates of hepatic metabolism and/or biliary excretion in children.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics observed for piperaquine in this study were similar to those previously reported for multiple dosing in healthy volunteers (20). Piperaquine exposure is known to be increased with the consumption of a high-fat, high-calorie meal (21). However, the low-fat food provided in the present study did not appear to have any noticeable effect on piperaquine pharmacokinetics compared to data from previous studies of unfed healthy volunteers (20).…”
Section: Discussionmentioning
confidence: 99%